A Comparison of Grammatical Errors Made by Thai EFL Undergraduate Students in Different Types of Essays - Inpanich, Pipittaporn; Chaya, Piyaporn; Wongsittikan, Nattapra; D. Evans, Mathew (Manutsat Paritat: Journal of Humanities, 2023)
This study aimed to enhance the writing proficiency of Thai EFL students by investigating the types and causes of grammatical errors made by Thai EFL undergraduate students across various essay types. This research examined four types of essays: a balanced opinion essay, an explanatory essay, a point-counterpoint essay, and an analysis essay. Fifteen students participated in this study, and a total of 60 essays were collected for analysis. The findings revealed that sentence fragment errors were most prevalent in explanatory essays. The misuse of nouns was most frequent in balanced opinion essays while subject-verb agreement mistakes had the highest occurrences in point-counterpoint essays. Spelling errors were the most common mistake in analysis essays. In terms of the causes, these grammatical errors may have stemmed from a combination of interlingual and intralingual interference. This study emphasizes the importance of Thai EFL instructors thoroughly understanding the distinctive features of each essay genre, and equipping students with a solid grasp of grammatical rules. Specific attention should be given to recurring grammatical errors including sentence fragments, the use of nouns, subject-verb agreement, and spelling when teaching essay writing to Thai EFL undergraduate students.